Transtibial Prosthesis Insert to Accommodate Residual Limb Volume Change - Raffla, Andre (Université d'Ottawa / University of Ottawa, 2025)
Within the first year after amputation, individuals with lower limb amputations often require multiple prosthetic sockets to accommodate changes in residual limb volume and shape. This frequent need for new sockets arises as the limb matures, posing a challenge for both amputees and prosthetists. Digital manufacturing technologies offer promising solutions to streamline this process. This thesis presents the development and pilot evaluation of a novel transtibial prosthesis insert, designed to provide a good socket fit without the need to manufacture an entirely new socket. The insert is created by digitally aligning the original socket shape with a newly designed socket shape based on the current limb morphology. This alignment allows for the digital creation of a 3D insert model that conforms to the original socket externally while matching the new limb shape internally. The insert is then 3D printed and integrated with the original socket to achieve proper fit. Various materials were tested to identify appropriate material and 3D printing parameters. An insert prototype was subjected to mechanical tests in accordance with current transtibial prosthesis socket testing methods to ensure durability under typical prosthesis loads. Additionally, a pilot trial with a transtibial amputee was conducted to evaluate user experience and satisfaction. Following testing, Ninjatek Cheetah Thermoplastic Polyurethane (NCT) was selected as the most appropriate material. The printing parameters were cubic print pattern and 35% infill. The results from mechanical testing and the pilot trial indicated that the insert is robust for use in daily activities, can accommodate residual limb volume change, and does not compromise on comfort and fit. This new approach offers an alternative to manufacturing a new socket, which saves time and costs for the end-user, prosthetist, and the health care system.
Keywords: Trans-tibial; prosthesis; insert; biomedical; pilot trial; mechanical testing; 3D printing; additive manufacturing; TPU; Slicer3D; transtibial; amputation